2003
DOI: 10.1080/00207450390220376
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and Neuroscience: History and New Perspectives

Abstract: History of the study of dissociation begins in the second half of the nineteenth century. It begins in the works of Hughlings Jackson and Pierre Janet, and markedly influences development of psychoanalysis and other psychological trends. According to the modern definition, dissociation represents a disturbance or alteration in the normally integrative functions of identity, memory, or consciousness. Dissociative symptoms occur mainly due to some traumatic events and probably cannot be generally explained on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 42 publications
7
42
0
Order By: Relevance
“…In this context, epileptiform activity has been suggested as an antibinding mechanism which is related to a failure of associative connections between neural assemblies (Medvedev, 2001(Medvedev, , 2002 and corresponding fragmentation of related mental representations characteristic for dissociative states. As a consequence chaotic selforganization during these processes may lead to pathological states such as epileptic paroxysms (Elger et al, 2000;Korn & Faure, 2003) or other manifestations of epileptiform activity when competitive neural assemblies remain disassociated or as unexpected original ideas due to successful creating of new associations during the chaotic competition (Elbert et al, 1994;Freeman, 1991Freeman, , 2000Freeman, , 2001Skarda & Freeman, 1987;Mölle et al, 1996;Lutzenberger et al, 1992;Bob, 2003). According to propositions of PDP models the competition among neural assemblies on the psychological level is correlated by competition among mental representations (e.g.…”
Section: Binding Of Neural Assemblies Chaos and Dissociation: A Neurmentioning
confidence: 99%
“…In this context, epileptiform activity has been suggested as an antibinding mechanism which is related to a failure of associative connections between neural assemblies (Medvedev, 2001(Medvedev, , 2002 and corresponding fragmentation of related mental representations characteristic for dissociative states. As a consequence chaotic selforganization during these processes may lead to pathological states such as epileptic paroxysms (Elger et al, 2000;Korn & Faure, 2003) or other manifestations of epileptiform activity when competitive neural assemblies remain disassociated or as unexpected original ideas due to successful creating of new associations during the chaotic competition (Elbert et al, 1994;Freeman, 1991Freeman, , 2000Freeman, , 2001Skarda & Freeman, 1987;Mölle et al, 1996;Lutzenberger et al, 1992;Bob, 2003). According to propositions of PDP models the competition among neural assemblies on the psychological level is correlated by competition among mental representations (e.g.…”
Section: Binding Of Neural Assemblies Chaos and Dissociation: A Neurmentioning
confidence: 99%
“…On the other hand, previous studies also showed that patients with temporal lobe epilepsy (TLE) experience several dissociative symptoms such as out of body experiences, near death experiences, depersonalization and fugue 6,7,22,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Connections of EEG abnormalities with several dissociative syndromes including dissociative identity symptoms have been described 22,24 . Temporal lobe epileptiform discharges and the limbic structures which are essential regions for generation of complex partial seizures can lead to these symptoms 3,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…There are also works that attribute the chaotic transitions to dissociative states in psychopathological conditions (Bob, 2009;Bob & Louchakova, 2015). They propose hypotheses relating the process of dissociation with the chaotic dynamics generated by discrete maps (Putnam, 1997) suggesting that the chaotic transitions may be related to dissociative states in the brain (Bob, 2003;. In addition, there are studies linking bipolar disorder with chaos (Gottschalk, Bauer & Whybrow, 1995;Bahrami et al, 2005;Buckjohn et al, 2010;Hadaeghi et al, 2013).…”
Section: Chaos and Mental Disordersmentioning
confidence: 99%